Butea monosperma bark extract mediated green synthesis of silver nanoparticles: Characterization and biomedical applications - Sutanuka Pattanayak; Md. Masud Rahaman Mollick; Dipanwita Maity; Sharmila Chakraborty; Sandeep Kumar Dash; Sourav Chattopadhyay; Somenath Roy; Dipankar Chattopadhyay; Mukut Chakraborty (Journal of Saudi Chemical Society, 2017)
The work deals with an environmentally benign process for the synthesis of silver nanoparticle using Butea monosperma bark extract which is used both as a reducing as well as capping agent at room temperature. The reaction mixture turned brownish yellow after about 24 h and an intense surface plasmon resonance (SPR) band at around 424 nm clearly indicates the formation of silver nanoparticles. Fourier transform-Infrared (FT-IR) spectroscopy showed that the nanoparticles were capped with compounds present in the plant extract. Formation of crystalline fcc silver nanoparticles is analysed by XRD data and the SAED pattern obtained also confirms the crystalline behaviour of the Ag nanoparticles. The size and morphology of these nanoparticles were studied using High Resolution Transmission Electron Microscopy (HRTEM) which showed that the nanoparticles had an average dimension of ∼35 nm. A larger DLS data of ∼98 nm shows the presence of the stabilizer on the nanoparticles surface. The bio-synthesized silver nanoparticles revealed potent antibacterial activity against human bacteria of both Gram types. In addition these biologically synthesized nanoparticles also proved to exhibit excellent cytotoxic effect on human myeloid leukemia cell line, KG-1A with IC50 value of 11.47 μg/mL. Keywords: Butea monosperma, Green route, Silver nanoparticles, Antibacterial, Anticancer